Childhood ovarian nonseminomatous germ cell tumors: A highly curable disease with few long‐term treatment‐related toxicities—Results of the French TGM95 study. Issue 9 (5th July 2021) - Pavone, Rossana; Pacquement, Hélène; Pasquet, Marlène; Sudour‐Bonnange, Hélène; Hameury, Fédéric; Sarnacki, Sabine; Chastagner, Pascal; Faure‐Conter, Cécile; Poirée, Marilyne; Taque, Sophie; Patte, Catherine; Fresneau, Brice
Abstract: We report survival and late effects analysis of TGM95 study for childhood (≤18 years) ovarian nonseminomatous germ cell tumors (NS‐GCT). Patients with localized tumors (FIGO‐stage IA) had no adjuvant treatment (low‐risk, LR). Patients with advanced‐stage received 3‐5 VBP (vinblastin‐bleomycin‐cisplatin) in intermediate‐risk group (IR: FIGO‐stage IC‐II‐III and AFP < 15 000 ng/mL) or 4‐6 VIP (etoposide‐ifosfamide‐cisplatin) in high‐risk group (HiR: metastatic or AFP ≥ 15 000 ng/mL). Seventy‐seven patients were included (median age = 12 years): 14 LR (13 FIGO‐stage IA, 1 retrospectively IC), 26 IR (12 IC, 12 II‐III, 2 not‐available) and 37 HiR (2 IA with AFP ≥ 15 000 ng/mL, 27 II‐III, 8 IV). After a median follow‐up of 13.4 years, 12 events (eight relapses) and six deaths (two GCT‐related, two due to acute myeloid leukemia and two noncancer related) occurred. All relapses (6 LR, 1 IR) occurred within 2 years. Four contralateral mature teratomas were observed within 8 years. Five‐year EFS and OS were 88.2% (95%CI = 79‐94%) and 94.6% (95%CI = 87‐98%). Seven patients (9%) had bilateral gonadectomy. Among 51 survivors at 2 years aged >15 years (median = 26 years) with remaining ovarian tissue, all had developed spontaneous puberty and 21 (41%) had at least one pregnancy (including two with infertility treatment). Among 69 patients treated with platinum‐based chemotherapy, chronic‐kidney‐disease was diagnosed in four patients (three after VIP) and significant ototoxicity occurred in three (all grade‐2). Childhood ovarian NS‐GCTs have an excellent prognosis with few late effects. The low‐intensive etoposide‐free VBP regimen could be an alternative in children with IR disease especially in cases of tumor rupture. The risk of contralateral mature teratoma needs regular monitoring of the remaining ovary.